Pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap Impulse Buying Mahasiswa - Mujianah, Siti; Fikri, Abdullah; Yakub, Rizky; F Sanjaya, Vicky (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
This study aims to identify and measure the effect of Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying of Raden Intan Lampung State Islamic University Students at Lazada.co.id and help in detailing how much the independent variable is related or affects the dependent variable. This research uses quantitative methods by collecting primary data through online questionnaire distribution using the Google Form platform. The population focus of this research is students of Raden Intan Lampung State Islamic University who have made purchases at Lazada.co.id, using a sample of 91 respondents and selected through non probability sampling. Specifically the purposive sampling technique, which allows researchers to select samples based on certain considerations, so as to ensure that the selected sample represents the relevant variations in the population. The results in this study indicate that Hedonic Shopping Motivation (X1) shows a positive but insignificant effect on Impulse Buying (Y). Meanwhile, Shopping Lifestyle (X2) shows a positive and significant influence on Impulse Buying (Y).